xPC speed control of DC servo - Mohd Noor, Samsul Bahari; Maizan, Mohd Azhar (Federation of Engineering Institutions of Islamic Countries, 2006)
Control system design is a tedious and laborious job where a lot of time is spends on modeling the system, testing and deploy real time systems. MATLAB is one of the powerful tools for these purposes. It has a graphical programming tool, Simulink and a numbers of toolboxes included xPC Target that makes modeling and simulation of complex systems relatively easy. The Real Time Workshop and xPC Target works together so it is possible to include an external physical system for real time application. In this paper, xPC environment has been utilized to control speed of a DC servo and found to perform well.